Raising Public Legal Awareness Through Consumer Protection Education in Digital Trade - Liliana Sandoparte; Sobia Bashir; Monalisa Pattanayak (CV. Global Cendekia Inti, 2025)
The rapid expansion of digital trade has increased consumer vulnerability to fraud, misinformation, and unfair business practices. This study examines the role of consumer protection education in raising public legal awareness in the digital era. The research adopts a qualitative normative approach based on a systematic review of recent scholarly literature. The findings show that consumer education significantly improves legal literacy, enabling individuals to recognize risks, understand their rights, and engage in safer digital transactions. Several studies highlight that legal awareness reduces fraud incidents and strengthens trust in e-commerce ecosystems. However, gaps remain in the accessibility and implementation of educational programs, particularly in developing countries. The study concludes that integrating legal education into digital literacy initiatives and strengthening regulatory frameworks are essential strategies for enhancing consumer protection. This research contributes to the development of a comprehensive model of consumer empowerment in digital markets.